Stalagmite multi-proxy evidence of wet and dry intervals in the middle Yangtze Valley during the last glacial period - Meng Wang (2023)
There continues to be debate on the wet and dry conditions in central China due to different geological archives and proxy interpretations. This study reconstructed multi-proxy sequences spanning intervals between 65 and 40 ka using high-precision Th-230 dates, which was carried out on a stalagmite from Yongxing cave in the middle Yangtze Valley located in the Meiyu belt, China. Merely according to the petrography of the sample, Heinrich (H) 5-H6, Dansgaard–Oeschger (DO) 9-DO18 (or even secondary changes including DO15a and DO15b; DO17a, DO17b, and DO17c) were directly identified alongside the oxygen isotope record. The δ13C, trace elements, mineralogical, and bio-geochemical proxies exhibited similar millennial changes to that of the δ18O. This provided an indication of responses to millennial-scale climatic events in the karst hydrological cycle, local environment, and soil vegetation; however, the sensitivities to these events differed. Petrographic analyses of the same stalagmite including scanning electrical microscope (SEM), X-ray diffraction (XRD), fluorescence intensity, the deposition rate, and the diameter index depicted a dry-cold climate during the H events, and a wet-warm climate during the DO cycles in the middle Yangtze Valley. These results are consistent with the peat records of Dajiuhu Lake in the same area. We suggest that a combination of Atlantic Meridional Overturning Circulation (AMOC) and El Niño-Southern Oscillation (ENSO) may exert a strong influence on the Meiyu region and the related precipitation.